Implementing Learner Experience Design in University Teaching - Christian Rogers (Journal of the Scholarship of Teaching and Learning)
The Learner Experience Design (LXD) framework aims to create engaging and relevant learning experiences by considering students' past, motivations, challenges, frustrations, emotions, and needs, as well as their interactions with faculty, staff, and other students. The LXD process involves three steps: research, design, and evaluation. During the research phase, instructors gather important insights through student interviews. In the design phase, they develop a plan for a learning experience. Finally, in the evaluation phase, they assess the effectiveness of the learning experience and plan for potential revisions. This article details a case study of a workshop series in which faculty members from universities spanning several countries utilized LXD with their students. It shares observations collected from workshop participants that indicate not only evidence of intended innovative curricular enhancements, but an unanticipated increase in student-teacher connection and motivation.